Perancangan Sistem Informasi pelayanan Paket Pernikahan Pada Mindo Wedding Organizer - Laraswati, Dewi; Marlina, Marlina (IJSE - Indonesian Journal on Software Engineering, 2019)
Abstract: Mindo Wedding Organizer is a business in the field of wedding and catering services that includes wedding planning consultations or other large events that serve catering, rental clothes and bridal makeup. In this study, researchers identified the problem using an Ishikawa diagram so that it was known the cause and effect of the existing problems. Next, the researchers propose a computerized system with the waterfall method. With Computerization System the problems that exist in this company, especially in terms of data processing can be resolved properly, and with a computerized system can be achieved an activity that is effective and efficient in supporting the activities of this company. Keywords: Wedding Package Services, Information Systems, Ishikawa, Waterfall